Frequency of del(12p) is commonly underestimated in myelodysplastic syndromes: results from a German diagnostic study in comparison with an international control group - Braulke, Friederike; Hofmann, Wolf-Karsten (Genes, chromosomes & cancer, 2015)
In myelodysplastic syndromes (MDS), deletion of the short arm of chromosome 12 (del(12p)) is usually a small abnormality, rarely detected as a single aberration by chromosome banding analysis (CBA) of bone marrow metaphases. Del(12p) has been described in 0.6 to 5% of MDS patients at initial diagnosis and is associated with a good to intermediate prognosis as a sole anomaly according to current scoring systems. Here, we present the results of a systematic del(12p) testing in a German prospective diagnostic study (clinicaltrials.gov: NCT01355913) on 367 MDS patients in whom CD34+ peripheral blood cells were analysed for the presence of del(12p) by sequential fluorescence in situ hybridization (FISH) analyses. A cohort of 2,902 previously published MDS patients diagnosed by CBA served as control. We demonstrate that, using a sensitive FISH technique, 12p deletion occurs significantly more frequently in MDS than previously described (7.6% by CD34+ PB-FISH vs. 1.6% by CBA, P < 0.001) and is often associated with other aberrations (93% by CD34+ PB-FISH vs. 60% by CBA). Additionally, the detection rate can be increased by repeated analyses in a patient over time which is important for the patient´s prognosis to distinguish a sole anomaly from double or complex aberrations. To our knowledge, this is the first study to screen for 12p deletions with a suitable probe for ETV6/TEL in 12p13. Our data suggest that the supplement of a probe for the detection of a 12p deletion to common FISH probe panels helps to avoid missing a del(12p), especially as part of more complex aberrations. © 2015 Wiley Periodicals, Inc.
Gesehen am 06.09.2017